Anti Lipidemic Effects of Cinnamon in Hyperlipidemia Adults - Dr. Muhammad Tahir Khalid (ACADEMIA International Journal for Social Sciences, 2025)
Hyperlipidemia is a major risk factor for cardiovascular diseases and remains a growing public health concern. Due to the limitations and side effects associated with synthetic lipid-lowering drugs, there is increasing interest in safe, natural alternatives. Cinnamon (Cinnamomum zeylanicum) contains polyphenolic compounds such as cinnamaldehyde and procyanidins, which possess antioxidant and metabolic regulatory properties that may contribute to improved lipid profiles. The present study evaluated the anti-lipidemic effects of cinnamon supplementation among hyperlipidemic adults. A randomized comparative clinical study was conducted on 40 participants aged 25–60 years from Sargodha, Faisalabad, Lahore, and Rawalpindi. Participants were divided into a Control Group (n=20), receiving no supplementation, and a Cinnamon Group (n=20), receiving 2 g/day of cinnamon powder in capsule form for 6 weeks. Lipid profile including total cholesterol, LDL-C, HDL-C, and triglycerides were assessed at baseline and post-intervention. After 8 weeks, the cinnamon group showed significant reductions in total cholesterol, LDL-C, and triglycerides, along with a meaningful increase in HDL-C, whereas the control group exhibited no significant changes. No adverse effects were reported, indicating good tolerability. These findings suggest that cinnamon supplementation has a beneficial impact on lipid metabolism and may be used as a safe, natural adjunct therapy for managing hyperlipidemia. Further large-scale and long-term clinical trials are recommended to validate these results.